1990
DOI: 10.1051/jphyscol:1990431
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of Amorphous Alloys by High Energy Mechanical Defofmation

Abstract: Resume -Le broyage B billes B haute energie a et6 utilise frequemment ces dernieres annees pour produire des alliages amorphes en alliant mecaniquement des elements pures cristallins ou en deformant mecaniquement des composes intermetallics. Le processus de broyage B billes est normallement caracteris6 par une temperature effective locale au site d'impact qui controle les transformations de structure survenant lors du broyage. A des intensites de broyage Blevees, la temperature effective serait telle que la pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…For Al based amorphous alloys, nanocrystals have first been deformation induced in shear bands of bent ribbons [4], but they have also been detected for ball-milled [5], cold rolled [6], and high pressure torsion strained samples [7]. Attempts to rationalize the deformation induced crystallization reactions have focused on two approaches.…”
Section: Introductionmentioning
confidence: 98%
“…For Al based amorphous alloys, nanocrystals have first been deformation induced in shear bands of bent ribbons [4], but they have also been detected for ball-milled [5], cold rolled [6], and high pressure torsion strained samples [7]. Attempts to rationalize the deformation induced crystallization reactions have focused on two approaches.…”
Section: Introductionmentioning
confidence: 98%
“…However, MGs will develop ordered structures if enough energy is supplied. Numerous studies have shown that nanocrystals can be formed under annealing [8], deformation [9], bending [10], nanoindentation [11] and ion or electron irradiation [12][13][14][15][16]. Although the specific mechanisms that induce partial crystallization are different in each of these cases, the general crystallization phenomena are typically associated with enhanced atomic mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of deformation-induced crystallization reactions include Fe-based amorphous alloys [12–16], amorphous Ni–P alloy [17], bulk amorphous Zr and Cu–Zr alloys, and amorphous Al alloys [1822]. The deformation techniques used so far include bending [23], ball milling [1416 24], cold rolling [12,2532], high-pressure torsion straining [18,33], nanoindentation [34], and uniaxial compression [35]. The results of intense deformation have demonstrated nanocrystals with number densities of up to 10 22 m −3 and average sizes of less than 10 nm, but the origin of the deformation-driven nanocrystallization remains an area of active research.…”
Section: Resultsmentioning
confidence: 99%